Eastern Europe between Transition and Accession: An Analysis of Reform Requirements - Daniel Piazolo (Kiel Institute of World Economics (IfW), 2000)
This paper examines the transition process within Eastern Europe and the integration process with the EU and shows that the requirements for the transition towards a market economy overlap with the requirements for EU accession. Furthermore, the economic situation of the candidate countries is examined and it is pointed out that there is a large gap in the economic development between the Central and Eastern European countries and the EU. The paper argues that the acceding transition countries still have substantial reform tasks ahead of them and that the expanding EU membership requires also considerable reforms within the EU to reduce the danger of standstill for European policy making.
Keywords: P20; F02; F15; 330; European integration; transition economies; regional integration; EU enlargement; acquis communautaire; Übergangswirtschaft; EU-Erweiterung; Systemtransformation; Osteuropa; Verfassungsreform; EU-Staaten